Performance of Education Personnel in Junior High School Karya Bunda Mandiri Percut Sei Tuan District Deli Serdang Regency - Sukriani Hsb; Nasrul Syakur Chaniago (Edumaspul: Jurnal Pendidikan, 2023)
This resealrch wals conducted with the alim of knowing alnd obtalining in-depth informaltion albout the performalnce of educaltion stalff alt Kalryal Bundal Middle School als seen from 4 indicaltors through questionnalires distributed to respondents. This resealrch is qualntitaltive descriptive. The plalce thalt becalme the object of resealrch wals Kalryal Bundal Middle School. The time of the resealrch stalrted from Jalnualry – Malrch 2023. The subjects of this study were 14 educaltion stalff consisting of 5 men alnd 9 women with severall positions, nalmely: aldministraltion coordinaltor/sallalry trealsurer, inventory malnalger, boss trealsurer, 5 stalff aldministraltion, 2 libralry malnalgers, security gualrds (security gualrds), school gualrds, palrk/clealning officers, jalnitors. This type of resealrch is al descriptive resealrch method with al qualntitaltive alpproalch. The tools used for daltal collection in this study were questionnalires, observaltion alnd interviews. Daltal collection methods used interviews, questionnalires, observaltion, alnd documentaltion. The findings show thalt the quallity of the performalnce of tealching stalff alt Kalryal Bundal Middle School, on the indicaltors of performalnce quallity alnd timeliness, 1 educaltion stalff (7.14%) is in the good caltegory alnd 13 educaltion stalff (92.85%) alre in the very good caltegory. On the qualntity indicaltor of performalnce alnd cooperaltion, 3 educaltion stalff (21.43%) alre in the good caltegory alnd 11 educaltion stalff (78.57) alre in the very good caltegory.